2021
DOI: 10.5540/tcam.2021.022.01.00109
|View full text |Cite
|
Sign up to set email alerts
|

Why Can We Observe a Plateau Even in an Out of Control Epidemic Outbreak? A SEIR Model With the Interaction of n Distinct Populations for Covid-19 in Brazil.

Abstract: This manuscript proposes a model of $n$ distinct populations interaction structured SEIR to describe the spread of COVID-19 pandemic diseases. The proposed model has the flexibility to include geographically separated communities as well as taking into account aging population groups and their interactions. We show that distinct assumptions on the dynamics of the proposed model lead to a plateau-like curve of the infected population,  reflecting collected data from large countries like Brazil. Such observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…This extension can describe, for example, the spread of the disease between neighborhoods and neighboring cities. Diffusion produces an increase in the period of the epidemic because, in each neighborhood and city, the peak of infection occurs at a different time [6], as we will see in our model when considering the interaction between two cities. For the results presented in Figure 2 we used N 1 = 211965 (data from the population of Rio Grande obtained through the website https://www.riogrande.rs.gov.br/pagina/284-anos-riogrande-mantem-forte-potencial-economico-e-turistico/ (Rio Grande City Hall)), β 11 = 1, γ 1 = 0.5, κ 1 = 0 (for simplicity, we do not consider death cases) and µ 1 = 0.001.…”
Section: A Single Isolated Population: Model Without the Interaction ...mentioning
confidence: 72%
See 2 more Smart Citations
“…This extension can describe, for example, the spread of the disease between neighborhoods and neighboring cities. Diffusion produces an increase in the period of the epidemic because, in each neighborhood and city, the peak of infection occurs at a different time [6], as we will see in our model when considering the interaction between two cities. For the results presented in Figure 2 we used N 1 = 211965 (data from the population of Rio Grande obtained through the website https://www.riogrande.rs.gov.br/pagina/284-anos-riogrande-mantem-forte-potencial-economico-e-turistico/ (Rio Grande City Hall)), β 11 = 1, γ 1 = 0.5, κ 1 = 0 (for simplicity, we do not consider death cases) and µ 1 = 0.001.…”
Section: A Single Isolated Population: Model Without the Interaction ...mentioning
confidence: 72%
“…Finally, it can be seen that the curve does not describe well the cases reported by the official data, since the real dynamics show an approximately linear growth. According to [6] this linear growth may be an indication of the spread of the disease to neighboring cities and between neighborhoods of the same city. This fact leads to anomalous growth dynamics, which motivates the investigation of models of interacting populations and fractional models.…”
Section: A Single Isolated Population: Model Without the Interaction ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Reinforcing our findings, a structured compartmental model (in agreement with data observed in large countries such as Brazil) indicated that maintenance of a high number of COVID-19 cases in Brazil could be supported by the geographical spread of the disease, which would occur from the state capitals to the interior of the country. 28 Nevertheless, there was little connection between the municipalities in the middle of the state (Jordão, Marechal Thaumaturgo, Porto Walter and Santa Rosa do Purus), which is a possible explanation for the lower rates/intensities of SARS in these cities (Figures 3 and 4). This can be explained by the low circulation of people between these municipalities, which would tend to give rise to low circulation of the disease.…”
Section: Discussionmentioning
confidence: 95%
“…Reinforcing our findings, a structured compartmental model (in agreement with data observed in large countries such as Brazil) indicated that maintenance of a high number of COVID-19 cases in Brazil could be supported by the geographical spread of the disease, which would occur from the state capitals to the interior of the country. 28 …”
Section: Discussionmentioning
confidence: 99%